Ekspresi Eufemisme dalam Surat Kabar di Kota Palu - Ali Karim; Julia Marfuah; Muhammad Aqil; Fadly A. Karim (Ranah: Jurnal Kajian Bahasa, 2024)
The topic discussed in this article is the use of euphemisms in newspapers. The aim is to describe the synonymy of euphemisms in newspapers in terms of collocation, distribution, emotive meaning and meaning components. The steps taken in this research include three stages, namely: (1) data collection stage, (2) data analysis stage, and (3), data analysis results presentation stage. The method used in collecting data is the siak method with note-taking technique. The methods used in data analysis are the matching method with referential matching techniques and the distributional method with techniques for direct elements, expansion techniques, and replacement techniques. The methods used in presenting the results of data analysis are formal methods and informal methods. The results of the research show that the use of euphemisms in newspapers is not perfectly synonymous with the linguistic form they replace based on analysis of collocation, distribution, emotive meaning and meaning components. Apart from that, the use of euphemisms in newspapers tends to hide certain intentions so as not to disturb the public. AbstrakTopik yang dibahas dalam artikel ini adalah penggunaan eufemisme dalam surat kabar. Tujuannya adalah untuk mendeskripsikan sinonimi eufemisme dalam surat kabar ditinjau dari kolokasi, distribusi, makna emotif, dan komponen makna. Langkah-langkah yang dilakukan dalam penelitian ini meliputi tiga tahap, yaitu: (1) tahap pengumpulan data, (2) tahap analisis data, dan (3) tahap penyajian hasil analisis data. Metode yang digunakan dalam pengumpulan data adalah metode siak dengan teknik catat. Metode yang digunakan dalam analisis data adalah metode padan dengan teknik padan referensial dan metode distribusional dengan teknik unsur langsung, teknik perluasan, dan teknik penggantian. Metode yang digunakan dalam penyajian hasil analisis data adalah metode formal dan metode informal. Hasil penelitian menunjukkan bahwa penggunaan eufemisme dalam surat kabar tidak sepenuhnya sinonim dengan bentuk kebahasaan yang digantikannya berdasarkan analisis kolokasi, distribusi, makna emotif, dan komponen makna. Selain itu, penggunaan eufemisme dalam surat kabar cenderung menyembunyikan maksud tertentu agar tidak meresahkan masyarakat.